The Effect of Seed-Borne Fungi and Epichloë Endophyte on Seed Germination and Biomass of Elymus sibiricus - Li, Xiu-Zhang; Song, Mei-Ling; Yao, Xiang; Chai, Qing; Simpson, Wayne R.; Li, Chun-Jie; Nan, Zhi-Biao (Frontiers in Microbiology, 2017)
The interactive effects of asexual Epichloë (formerly known as Neotyphodium) endophytes isolated from Hordeum brevisubulatum, Elymus tangutorum and Achnatherum inebrians, and seed-borne fungi on Elymus sibiricus seeds, were determined by an in vitro study using supernatants from liquid cultures of the endophyte strains. In an 8 week greenhouse study, the effects on the seedlings growth was measured. The in vitro study was carried out with the seed-borne fungi Alternaria alternata, Bipolaris sorokiniana, Fusarium avenaceum, and a Fusarium sp. isolated from E. sibiricus. Different concentrations and combinations of the liquid cultures of endophytic fungi enhanced the interim germination, germination rate, length of coleoptile and radicle, and seedling dry weight of E. sibiricus under stress from seed-borne fungi. In the greenhouse study, different concentrations of the supernatant of the endophytes from H. brevisubulatum and E. tangutorum but not A. inebrians, signficantly (P < 0.05) enhanced E. sibiricus seed germination. There was no significant (P > 0.05) increase of the tiller numbers after 2 weeks. However, later on, there were significant (P < 0.05) increases in tiller number (4–8 weeks), seedling height (2–8 weeks) and dry weight (2–8 weeks). The application of Epichloë endophyte culture supernatants was an effective strategy to improve seed germination and growth under greenhouse conditions.